The Influence of My Hatta Online Registration System Innovation on Patient Satisfaction - Halwa Syahrastani; Boni Saputra (Al-Qalam Institue, 2026)
Patient satisfaction represents a fundamental measure of healthcare service quality, yet prolonged registration procedures and inefficient administrative processes continue to undermine patients' experiences in hospital settings. In response to these challenges, DR. Drs. M. Hatta Brain Hospital in Bukittinggi introduced the My Hatta online registration system as part of its digital transformation initiative to improve service accessibility and operational efficiency. This study investigated the influence of the My Hatta online registration system innovation on patient satisfaction. A quantitative associative design employing a cross-sectional approach was adopted. Data were obtained from 100 patients selected through accidental sampling using a structured questionnaire and analyzed using descriptive statistics and simple linear regression with IBM SPSS. The findings revealed that the innovation of the My Hatta system was perceived positively (TCR = 83.08%) and exerted a significant positive effect on patient satisfaction (β = 0.793, p < 0.001), accounting for 62.9% of the explained variance (R² = 0.629). Patients who perceived the application as useful, easy to use, compatible with their needs, capable of enhancing the hospital's image, and providing observable benefits reported higher levels of satisfaction. These findings demonstrate that effective digital innovation is a critical driver of patient-centered healthcare quality in specialized hospitals. The study advances the literature by extending the application of the Technology Acceptance Model and innovation theory within specialized healthcare contexts while offering practical insights for optimizing digital registration systems and strengthening patient-oriented healthcare management.